Implementasi Program KKN dalam Pemberdayaan Masyarakat Desa Sialaman: (Studi Kualitatif pada Aspek Kesehatan, Pendidikan, UMKM dan Lingkungan) - Salahuddin Harahap; Rofiil Harahap; Pebriansyah Siregar; Rahma Mahrani Sam Harahap; Miftahul Hasanah Siregar; Cahya Amandasari; Winda Siregar (BADAN PENERBIT STIEPARI PRESS, 2026)
This study aims to analyze the implementation of the Community Service Program (KKN) in empowering the people of Sialaman Village through a qualitative approach. The research focuses on four main aspects: health, education, Micro, Small, and Medium Enterprises (MSMEs), and the environment. Data were collected using participatory observation, in-depth interviews, and documentation with villagers, local leaders, and KKN participants. The findings show that in the health aspect, the program successfully increased public awareness of clean living habits and the importance of regular health check-ups. In education, tutoring activities and digital literacy programs for children fostered motivation and expanded basic knowledge. In the MSME sector, mentoring activities for household businesses improved understanding of simple financial management, marketing strategies, and digital technology utilization. Meanwhile, in the environmental aspect, the community actively participated in greening projects, waste management, and cleanliness campaigns. Overall, the implementation of KKN had a positive impact on strengthening community capacity, although challenges remain in terms of limited facilities, funding, and program sustainability after KKN ends. Thus, the KKN program proves to be a strategic instrument in promoting sustainable community empowerment in rural areas.